SOCIAL NETWORKS AS TOURIST PROMOTION OF THE CHARAPOTÓ SPAS - Zambrano, Lilia Moncerrate Villacis; Delgado, Alexandra Scheznarda Anchundia (Seven Editora, 2025)
The main objective of this research was to analyze how social networks can be used for tourism promotion of the Charapotó spas, in order to identify the most effective strategies and evaluate their impact on attracting tourists. The research had a focus quantitative and qualitative, the design was descriptive, the technique used was the survey, a non-probabilistic convenience sampling was applied, the sample obtained was 80 people, subsequently the spss 26 was used to measure the reliability and tabulate the data, yielding a reliability of 0.943, it was concluded that social networks were consolidated as key tools for the tourist promotion of the Charapotó spas, allowing not only greater visibility of local attractions, but also the creation of direct links with potential visitors. , these platforms offer a massive reach, enabling the dissemination of visual and dynamic content that highlights the unique characteristics of the destination, in addition, their strategic use enhances interaction with the target audience, favoring the positioning of the destination in the tourism market and contributing to the local economic development, the implementation of effective campaigns on social networks can transform Charapotó into a competitive destination, attracting both national and international tourists. DOI: https://doi.org/10.56238/sevened2025.021-069